Update on the comorbidity of attention-deficit/hyperactivity disorder (ADHD) and pervasive developmental disorder (PDD) (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Nowadays, the attention-deficit hyperactivity disorder/pervasive developmental disorder (ADHD/PDD) comorbidity is not accepted by DSM-IV criteria. However, researchers from both areas put in check this impossibility and describe patients who have both clinical aspects from attention-deficit hyperactivity disorder (ADHD) and pervasive developmental disorder (PDD). In this article we search for this findings proposing new insights on this assumption. OBJECTIVE: To perform a selective review of the most significant studies in order to compile an update on comorbidity ADHD and PDD. METHOD: All papers from 2000 to 2005 in English obtained through Medline search, covering ADHD symptoms in patients with PDD, autistic symptoms in patients with ADHD and the double diagnosis of ADHD and PDD using the terms "ADHD", "pervasive", "autism", "ADD", "Asperger" e "PDD". RESULTS: Ten papers attending the criteria were found. Although there are only few studies with small samples, different authors have identified a subgroup of patients with PDD portraying more severe symptoms of ADHD, who apparently respond less well to stimulants CONCLUSION: Although DSM-IV criteria do not allow the diagnosis of this comorbidity, some results suggest that this possibility should not be discarded.